Bringing interactive elements into classes: Augmented reality-based learning media development for electrical measurement subjects in vocational education - Murtita Mardiah Putri; Noverta Effendi; Fitri Farida; Gulzhaina Kuralbayevna Kassymova (Journal of Computer-based Instructional Media, 2024)
This study aims to develop and evaluate Augmented Reality (AR)-based learning media to improve student interest at SMKN 1 Kuantan Mudik. AR, which integrates virtual objects into the real world, is expected to enrich the learning experience through innovative visual and interactive elements. This research employs a Research and Development (R&D) which includes preliminary research, prototype creation, student response assessment, and systematic reflection. The AR-based learning media prototype was developed using Assemblr Edu software and evaluated by media experts, content specialists, and students. The validation results indicate that the media is highly viable, receiving a score of 92.7% from content experts and media specialists. Student trials produced ratings of 88.9% for effectiveness and 90.3% for engagement. The findings demonstrate that AR-based learning media significantly enhance student interest and involvement in the learning process. This study concludes that augmented reality learning media substantially improve educational experiences in vocational settings, showing potential for broader implementation across various subjects. However, this research is limited to expert validation processes and primarily focuses on student responses rather than measuring learning outcomes. This study is anticipated to provide a foundation for developing more comprehensive and effective learning media.